Ascertainment of familial ovarian cancer in the Aberdeen Genetic Clinic. Issue 3 (March 1996) - Gregory, H; Schofield, A; de Silva, D; Semper, J; Milner, B; Allan, L; Haites, N
Abstract : Ovarian cancer is the fifth most common malignancy in women in the UK. Patients with a family history including ovarian cancer make up nearly 15% of family cancer referrals to the Genetic Clinic in Aberdeen. To date, only one pedigree has been suitable for linkage studies, which has enabled us to target screening more accurately at those people at highest risk. Following discovery of a strong candidate for the BRCA1 gene, direct mutation testing may soon be possible. People who seek testing will require further counselling. Therefore we anticipate an increased demand on both clinical and laboratory resources, but more accurate ascertainment of high risk subjects should lead to more appropriate targeting of screening services.